The mediating effect of work-life balance on the relationship between work culture and employee well-being - Stankevičienė, Asta; Tamaševičius, Virginijus; Diskienė, Danuta; Grakauskas, Žygimantas; Rudinskaja, Liana (Journal of Business Economics and Management, 2021)
This article tends to fill the existing knowledge gap in understanding if work-life balance (WLB) can not only make a direct impact on employee well-being, but also play a mediating role between work culture and well-being. The purpose of this study was to investigate the mediating effect of WLB on the relationship between the structural dimensions of work culture – temporal flexibility, supportive supervision and operational flexibility – and employee well-being. The data were collected on the basis of a survey of employees employed by business and public sector organisations in Lithuania. The research revealed that all the components of work culture were important factors in defining employee well-being, had a strong direct impact on well-being and affected WLB. The results demonstrated that a direct effect of work culture on well-being was much stronger than the one moderated by an indirect effect of WLB. The findings also suggest that family-friendly culture can help employees to reach a better WLB, which, in its turn, assists employees in feeling higher satisfaction with general well-being at work. The current study expands the role of WLB as a mediator in organisational settings and its findings may be important for practitioners who seek to improve the performance of their organisation by enhancing the well-being of employees.